Function of the oxidative burst in hypersensitive disease resistance. - Tenhaken, R (1995)
Microbial elicitors or attempted infection with an avirulent pathogen strain causes the rapid production of reactive oxygen intermediates. Recent findings indicate that H2O2 from this oxidative burst plays a central role in the orchestration of the hypersensitive response: (i) as the substrate driving the cross-linking of cell wall structural proteins to slow microbial ingress prior to the deployment of transcription-dependent defenses and to trap pathogens in cells destined to undergo hypersensitive cell death, (ii) as a local threshold trigger of this programmed death in challenged cells, and (iii) as a diffusible signal for the induction in adjacent cells of genes encoding cellular protectants such as glutathione S-transferase and glutathione peroxidase. These findings provide the basis for an integrated model for the orchestration of the localized hypersensitive resistance response to attack by an avirulent pathogen.